PENANAMAN NILAI-NILAI KARAKTER (AKHLAK MULIA) DI TPA-TPSA NAGARI TIGO SUNGAI INDERA PURA - Alfian, Muhammad; Angela, Lia; Anzalina, Hofifah; Saputri, Utari Aulia Tianda; Saslina, Tri (Institut Agama Islam Negeri Kerinci, 2024)
This Community Service is intended as a preventive effort to reduce the morals of TPA-TPSA students. The impact in question is a reduction in students' ethics and concern for each other. Preventive efforts that are expected to touch the root of the problem are the application of character values to build noble moral behavior in students. In general, cultivating character values can be implemented by: 1). Building student character by increasing their sense of caring for others. The real step that can be taken is the formation of a cadre of students to become role models for students in instilling noble character values. As exemplary figures, cadres need to be equipped with knowledge, attitudes, behavior and understanding skills related to implementing noble moral character appropriately and intelligently. 2). Building Character through habituation, one of the habituation activities can be initiated through a learning program.